Forecasting on the Collapse of Rational Speculative Bubble in Hang Seng, Nikkei 225 and S&P 500 in 2018 - Nurfadhlina Abdul Halim; Nurharyanti Borhan; Nadhirah Gazali; Wan Muhammad Amir W. Ahmad (Academy of Sciences Malaysia, 2024)
Volume 12 Special Issue :6